2019
DOI: 10.1073/pnas.1817711116
|View full text |Cite
|
Sign up to set email alerts
|

A bacteria-based genetic assay detects prion formation

Abstract: Prions are infectious, self-propagating protein aggregates that are notorious for causing devastating neurodegenerative diseases in mammals. Recent evidence supports the existence of prions in bacteria. However, the evaluation of candidate bacterial prion-forming proteins has been hampered by the lack of genetic assays for detecting their conversion to an aggregated prion conformation. Here we describe a bacteria-based genetic assay that distinguishes cells carrying a model yeast prion protein in its nonprion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 40 publications
9
37
0
Order By: Relevance
“…We utilized the computational program PLAAC (49) to identify novel cPrDs. Although PLAAC's underlying algorithm was trained on yeast PrDs, it has recently proven successful in facilitating the identification of prions in Bacteria (45,76). Taken with our work here, in which PLAAC also enabled the identification of likely PrDs in Archaea, this speaks to the chemically conserved nature of at least a subset of (c)PrDs (amyloidforming) across all three domains of life.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…We utilized the computational program PLAAC (49) to identify novel cPrDs. Although PLAAC's underlying algorithm was trained on yeast PrDs, it has recently proven successful in facilitating the identification of prions in Bacteria (45,76). Taken with our work here, in which PLAAC also enabled the identification of likely PrDs in Archaea, this speaks to the chemically conserved nature of at least a subset of (c)PrDs (amyloidforming) across all three domains of life.…”
Section: Discussionsupporting
confidence: 61%
“…The coordinates of bacterial PrD from transcription termination factor Rho (Clostridium botulinum) and single-stranded DNA-binding protein SSB (Campylobacter hominis) were obtained from Yuan and Hochschild 2017 and Fleming et. al 2019, respectively (45,76). The PrD sequences were programmatically extracted from the full length fasta sequences of these proteins obtained from Uniprot.…”
Section: Sequence Analysis Of Experimentally Tested Archaeal Cprds Anmentioning
confidence: 99%
“…1 E ) suggests that, while the ability of SSB to drive LLPS is not necessarily essential for cell viability under stress-free laboratory conditions, it confers important adaptive advantages in free-living bacteria, such as the adaptability to environmental stress and related DNA damage. In line with our conclusions, a recent work using a novel, ClpB disaggregase-based genetic test showed that a segment of the Campylobacter hominis SSB IDR can form prion-like condensates in live E. coli cells ( 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the first bacterial protein capable of prion formation (the Clostridium botulinum global transcriptional terminator Rho [59]) and the first viral protein exhibiting prion-like self-propagating activity (formed by the baculovirus LEF-10 protein [78]) were discovered, suggesting that prion-based mechanisms for phenotypic diversification may be more pervasive than originally thought. We expect that more of these elements will be discovered with the development of new genetic tools to characterize and validate putative prions from other organisms [117,163].…”
Section: Evolutionmentioning
confidence: 99%